Numerical Analysis of Light Non-Resonant Transmission Through a Sub-Wavelength Slit at Angular Incidence - Kh. Sahakyan; Kh. V. Nerkararyan
Numerical analysis revealed that the dependence of transmitted intensity through a subwavelength slit, milled in thin metal screen on the angle of incidence is divided into two different zones by the supreme angle. In the first zone, the intensity of the non-resonant extraordinary transmission is described by a weak non-monotonic curve, while a rapid decline is seen in the second zone. The supreme angle does not depend on incident wavelength, slit width, metal screen thickness or metal type, and equals to 62° for p-polarized light and 44° for s-polarized light. Independently of the structural parameters and wavelength, the distributions of transmitted wave fields are represented by the Hankel functions and are homogeneous by angle.
Keywords: Physics; Electronic structure and electrical properties of surfaces